Development, delivery, and evaluation of the Texas Epidemic Public Health Institute pilot infection control lecture series - Ruch, Kayla E.; Rodriguez, Anabel; Rios, Janelle; Ostrosky-Zeichner, Luis; Brown, Eric L. (Frontiers in Public Health, 2025)
IntroductionThe Texas Epidemic Public Health Institute (TEPHI) aims to keep Texans healthy and the economy strong by preparing for the next infectious disease outbreak. TEPHI’s Small Rural Healthcare Preparedness core developed, delivered, and evaluated a pilot infection prevention and control webinar series called Infection Control for rural-serving health professionals and organizations based on infection prevention and control field best practices.MethodsData from the first year of the Infection Control series was collected through attendee registration forms, attendance records, knowledge, and post-lecture evaluation surveys using Qualtrics. The data were analyzed using Qualtrics software. Lectures were free and open to the public across disciplines. The material was promoted through public health channels with promotional flyers.Results1,105 individuals attended or viewed the Infection Control series. Despite a generally low response rate to evaluation surveys, feedback was consistently positive. Participants noted a “high likelihood of future TEPHI infection prevention and control lecture attendance.” The feedback informed improvements for the second year of the series.ConclusionAttendees of the Infection Control series gained a deeper understanding of relevant policies, procedures, and practices. By providing essential, accessible education on infection prevention and control at no cost, healthcare systems, administrators, and providers in rural healthcare systems across Texas have acquired the necessary knowledge to establish and maintain a safe environment for patients and staff in healthcare settings.